Bhabani Bhattacharya’s writings with Women Sufferings and Empowerment - Pathak, Dr. Rashmi (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Bhabani Bhattacharya is an excellent Indo- Anglo-Saxon novellist of this time. He has earned world-wide honor and his books have appeared in twenty six languages sixteen of that ar European. He has won the in demand Sahitya Akademy award for 1967 for his novel `Shadow from Ladakh’ that may be a worth and due honour done to the genius of Dr. Bhattacharya.